Keterampilan Mengolah Bahan Makanan dalam Film Little Forest Karya Junichi Mori - Rahakjani, Dwi Novi (Vocational College of Diponegoro University, 2021)
This research is entitled “Processing Foodstuffs Skills in the Little forest Movie by Junichi Mori”. The purpose of this research was to examine the skills of the Japanese people in processing foodstuffs in Junichi Mori's Little forest movie. The method used in this research is note taking method, descriptive analysis method and informal method. The theory used in this study is the Literary Gastronomy theory proposed by Endraswara and the Semiotic theory proposed by Danesi. The results showed that there were several skills in processing foodstuffs based on the food they were processed, 1) amazake which was processed using porridge and koji, 2) stir-fried akebi which was processed using ingredients from akebi skin and cooked using sabuji style, 3) hoshiimo made from dried sweet potatoes, 4) shimi daikon made from radish dried in cold air, 5) Hoshigaki, which is dried persimmon made from kind of astringent persimmons. in the Little Forest movie is shown the process of processing traditional foodstuffs. the unique thing is that the Japanese people in the little forest film not only use cooking utensils but also take advantage of the air temperature to process food.